Seroma after sternal wound debridement: Case report - Julia Glizevskaja; Mohammed Abbas; Nnamdi Nwaejike (Journal of Surgery and Surgical Research - Peertechz Publications, 2021)
Seroma formation is a common complication of any surgery producing a significant dead space or causing disruption of the lymphatic drainage. Although this is uncommonly reported in cardiac surgery. Such collections can cause localized pain, wound dehiscence, infection and can reoccur frequently, requiring multiple interventions. We present case of large sternal wound seroma after wound debridement with Computed tomography imaging for the patient, that initially underwent Coronary artery bypass grafting.